Advances in molecular mechanism of HPV16 E5 oncoprotein carcinogenesis - Chen, Biqing; Zhao, Liping; Yang, Rulin; Xu, Tianmin (Archives of biochemistry and biophysics, 2023)
For a considerable duration, cervical cancer has posed a significant risk to the well-being and survival of women. The emergence and progression of cervical cancer have garnered extensive attention, with prolonged chronic infection of HPV serving as a crucial etiological factor. Consequently, investigating the molecular mechanism underlying HPV-induced cervical cancer has become a prominent research area. The HPV molecule is composed of a long control region (LCR), an early coding region and a late coding region.The early coding region encompasses E1, E2, E4, E5, E6, E7, while the late coding region comprises L1 and L2 ORF.The investigation into the molecular structure and function of HPV has garnered significant attention, with the aim of elucidating the carcinogenic mechanism of HPV and identifying potential targets for the treatment of cervical cancer. Research has demonstrated that the HPV gene and its encoded protein play a crucial role in the invasion and malignant transformation of host cells. Consequently, understanding the function of HPV oncoprotein is of paramount importance in comprehending the pathogenesis of cervical cancer. E6 and E7, the primary HPV oncogenic proteins, have been the subject of extensive study. Moreover, a number of contemporary investigations have demonstrated the significant involvement of HPV16 E5 oncoprotein in the malignant conversion of healthy cells through its regulation of cell proliferation, differentiation, and apoptosis via diverse pathways, albeit the precise molecular mechanism remains unclear. This manuscript aims to provide a comprehensive account of the molecular structure and life cycle of HPV.The HPV E5 oncoprotein mechanism modulates cellular processes such as proliferation, differentiation, apoptosis, and energy metabolism through its interaction with cell growth factor receptors and other cellular proteins. This mechanism is crucial for the survival, adhesion, migration, and invasion of tumor cells in the early stages of carcinogenesis. Recent studies have identified the HPV E5 oncoprotein as a promising therapeutic target for early-stage cervical cancer, thus offering a novel approach for treatment. [Display omitted] •HPV16 E5 oncoprotein plays an important role in tumor progression.•HPV16 E5 oncoprotein promotes tumor progression in several ways.•Potential therapeutic approaches targeting HPV16 E5 signaling pathway.•Therapies targeting HPV16 E5 oncoprotein.